2013
DOI: 10.2147/ijwh.s40473
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in hypertensive disorders of pregnancy in the North Indian population

Abstract: Introduction:Hypertensive disorders complicating pregnancy seriously endanger the safety of the mother and fetus during pregnancy. Very few studies have explored hypertensive disorders of pregnancy in India, even though this disease has been associated with adverse maternal and perinatal outcomes. This study aimed to analyze the disease pattern and risk factors associated with the disorder and assess the maternal and fetal outcomes in cases of hypertensive disorders of pregnancy.Subjects and methods:This case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
35
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 16 publications
(14 reference statements)
18
35
6
2
Order By: Relevance
“…Ascites was observed in 2.8%, pleural effusion in 1.2%, HELLP syndrome in 0.8%, cortical venous thrombosis in 2.8% and duodenal perforation in one patient [16]. Prakash et al [10] reported HELLP syndrome in 7.5% of cases of pre eclampsia whereas Sachan et al [17] in 2013 reported it to be 3.07% [10][11][12][13][14][15][16][17]. All these additional features worsen the pregnancy outcome and are required to be watched for meticulously.…”
Section: Discussionmentioning
confidence: 99%
“…Ascites was observed in 2.8%, pleural effusion in 1.2%, HELLP syndrome in 0.8%, cortical venous thrombosis in 2.8% and duodenal perforation in one patient [16]. Prakash et al [10] reported HELLP syndrome in 7.5% of cases of pre eclampsia whereas Sachan et al [17] in 2013 reported it to be 3.07% [10][11][12][13][14][15][16][17]. All these additional features worsen the pregnancy outcome and are required to be watched for meticulously.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in a study done by Sachan R et al, 43.70% of cases had weight >2.5kg, 50% had weight 1.5kg-2.5kg, 6.33% had weight <1.5kg. 13 Also Gawde A et al study had 75% cases with fetal birth weight ≥2.5kg and 25% cases had fetal birth weight <2.5kg. In patients with hypertensive disorder of pregnancy, the growth retardation of the fetus occurs due to decreased utero-placental blood flow and ischemia.…”
Section: Fetal Weight In Grams At Birth Of Babies Delivered To Studymentioning
confidence: 95%
“…A recent study revealed that excessive placental secretion of soluble fms-like tyrosine kinase-1 may contribute to endothelial dysfunction, hypertension and proteinuria in preeclampsia (5). Preeclampsia can lead to acute maternal complications such as progression to eclampsia, acute renal or hepatic failure, pulmonary edema, cardiovascular disorders, intracranial hemorrhage, disseminated intravascular coagulation and HELLP syndrome (hemolysis-elevated liver enzymes and low platelet count) (1,2).…”
Section: Introductionmentioning
confidence: 99%